Operational Risk Assessment Towards the Integration of Primary Health Care Services at Sungai Rangit Community Health Center using the ISO 31000 (2018) Perspective - Lesmana, Iwan Setyo; Ellina, Agusta Dian; Indasah, Indasah (Indonesian Journal of Global Health Research, 2025)
Primary Healthcare Service Integration (PHSI) at Community Health Centers aims to integrate primary healthcare services at Community Health Centers, Sub-Centers, and Integrated service posts for a more comprehensive and integrated approach. Sungai Rangit Community Health Center in West Kotawaringin Regency is planned to implement PHSI in 2024. However, a preliminary study has shown several issues that need to be anticipated, especially in terms of planning and budgeting, organizational governance, and staff assignment. This study aims to explore the operational risks faced by Sungai Rangit Community Health Center so that the implementation of PHSI can run smoothly. This research uses a qualitative descriptive approach. Data was collected through Focus Group Discussions (FGD) involving 59 employees of Sungai Rangit Community Health Center and triangulated interviews with health department employees and qualified risk management experts. The study collected qualitative data through FGDs and document analysis, involving health center employees and policy documents. Triangulation with district officials and risk management experts ensured validity. Data were refined, categorized, and analyzed iteratively, leading to a prioritized risk assessment for healthcare integration while maintaining ethical considerations. The study identified 5 main operational risks that need to be anticipated, namely: 1) risk of unavailable budget; 2) risk of invalid health data; 3) risk of sub-standard work plan preparation; 4) risk of internet connection down; and 5) risk of employee demotivation. Village governments need to allocate budgets for the needs of cadres to conduct household data collection. Cluster Heads need to assist cadres in conducting data collection and filling out the LOCAL AREA MONITORING dashboard. WiFi access in the Community Health Center environment needs to be improved to support internet-based community health center operations.